Synthesis and Kinematics Analysis of a 2T1R Parallel Mechanism that Can be Used for Spreading Tray Adjustment - Hao Lin; Zhixin Shi; Yufeng Luo; Meiyan Ye; Dongfu Xie (Jixie chuandong)
The type synthesis problem of the spreading tray adjustment mechanism in the rice transplanting machine is analyzed， by the topological design theory and method of parallel mechanism based on Position and orientation characteristics set， 14 types of 3-degree-of-freedom 2T1R parallel mechanisms driven by moving pair are synthesized for the spreading tray adjustment mechanism. Considering the practical application requirements， a mechanism with strong practicality is selected， and the topological feature analysis and kinematic analysis are carried out for this mechanism， which lays the theoretical foundation for the subsequent specific structure design.